The Use of Liquid Organic Fertilizer As Growth Media and Production of Kangkung (Ipomoea reptans Poir) Hydroponics - Dali Andrian; Ahmad Rafiqi Tantawi; Abdul Rahman (Budapest International Research and Critics University, 2019)
This study aims to determine the effect of different concentrations of liquid fertilizer with hydroponic planting media on kale production. The research method used was Randomized Completely Factorial Design with 2 factors: POC cocoa skin and cocoa poc added with cow dung. This study consisted of 16 treatment combinations each repeated 2 times. So there are 32 units of the whole experiment. Parameters observed include: percentage of growth, plant height, number of leaves (leaf), leaf area (), measuring leaf color, wet weight of harvest, wet weighted weighing, root length measurement. Based on the results of research that has been carried out can be concluded as follows: Provision of liquid organic fertilizer from cocoa leather and organic fertilizer liquid cow dung on the growth and production of kale plants showed unequal generative growth. The dosage of liquid organic fertilizer (POC) given by kangkung plantation has no effect on the increase of observed parameters from plant height, leaf number, leaf color, leaf area, and wet weight of the plant. In the excess of nutrient elements